Postcolonial biblical interpretation reframing Paul - Punt, J. 1962- (Leiden Boston Brill, 2015)
Front Matter -- Introduction -- Possibilities and Prospects of Postcolonial Biblical Criticism: Doing Mind and Road Mapping -- Postcolonial Readings, or Not? Obvious or Impossible? -- Postcolonial Theory as Academic Double Agent? Power, Ideology and Postcolonial Hermeneutics -- Competing Missions in Acts. Countervailing “Missionary” Forces: Empire and Church in Acts -- Paul and Postcolonial Hermeneutics: Marginality and/in Early Biblical Interpretation (2Cor 10–13) -- Postcolonial Clashing with Empire in 1Thessalonians 4–5 -- Paul, Power and Philemon: “Knowing Your Place” -- Paul, Body, and Resurrection in an Imperial Setting. Considering Hermeneutics and Power -- Negotiating Creation in Imperial Times (Romans 8:18–30) -- Conclusion: Pauline Agency in Postcolonial Perspective: Subverter of, or Agent for Empire? -- Epilogue -- Bibliography -- Index.
In Postcolonial biblical interpretation Jeremy Punt reflects on the nature and value of the postcolonial hermeneutical approach, as it relates to the interpretation of biblical and in particular, Pauline texts. Showing when a socio-politically engaged reading becomes postcolonial, but also what in the term postcolonial both attracts and also creates distance, exegesis from a postcolonial perspective is profiled. The book indicates possible avenues in how postcolonial work can be helpful theoretically to the guild of biblical scholars and to show also how it can be practiced in exegetical work done on biblical texts
Includes bibliographical references (p. 231-256) and index
Keywords: Bible -- Postcolonial criticism; Bible -- Postcolonial criticism